2020
DOI: 10.1042/bcj20200128
|View full text |Cite
|
Sign up to set email alerts
|

Nek7 conformational flexibility and inhibitor binding probed through protein engineering of the R-spine

Abstract: Nek7 is a serine/threonine-protein kinase required for proper spindle formation and cytokinesis. Elevated Nek7 levels have been observed in several cancers, and inhibition of Nek7 might provide a route to the development of cancer therapeutics. To date, no selective and potent Nek7 inhibitors have been identified. Nek7 crystal structures exhibit an improperly formed regulatory-spine (R-spine), characteristic of an inactive kinase. We reasoned that the preference of Nek7 to crystallise in this inactive conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Although some reported inhibitors have shown inhibition of NEK7-mediated inflammasome activation, no published works have shown screening of highly selective and potent inhibitors of NEK7. The latest research showed that use of conventional methods led to failed designs of NEK7 inhibitors owing to its unique conformation and high similarity to its paralog NEK6 ( Byrne et al, 2020 ). Then, this group developed a novel strategy using SRS mutations of NEK7 , which is a promising starting point for developing potent inhibitors targeting NEK7 ( Byrne et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some reported inhibitors have shown inhibition of NEK7-mediated inflammasome activation, no published works have shown screening of highly selective and potent inhibitors of NEK7. The latest research showed that use of conventional methods led to failed designs of NEK7 inhibitors owing to its unique conformation and high similarity to its paralog NEK6 ( Byrne et al, 2020 ). Then, this group developed a novel strategy using SRS mutations of NEK7 , which is a promising starting point for developing potent inhibitors targeting NEK7 ( Byrne et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latest research showed that use of conventional methods led to failed designs of NEK7 inhibitors owing to its unique conformation and high similarity to its paralog NEK6 ( Byrne et al, 2020 ). Then, this group developed a novel strategy using SRS mutations of NEK7 , which is a promising starting point for developing potent inhibitors targeting NEK7 ( Byrne et al, 2020 ). However, the kinase activity inhibition of NEK7 might have no effect on NLRP3 inflammasome activation ( Shi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As cell cycle kinases, NEKs are related to the mitotic regulator ‘never in mitosis, gene A’ (NIMA) 6,7 and regulate the cell cycle progression from the G2 to M phase 8,9 . NEKs are associated with multiple cancers 10,11 . Furthermore, their involvement in specific aspects of microtubule function and the DNA damage checkpoint, a key target pathway for cancer drugs, has led to considerable interest in mitotic enzymes as candidate cancer drug targets.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 NEKs are associated with multiple cancers. 10 , 11 Furthermore, their involvement in specific aspects of microtubule function and the DNA damage checkpoint, a key target pathway for cancer drugs, has led to considerable interest in mitotic enzymes as candidate cancer drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a prior study revealed the decrease of serum level of miR‐23a in type 2 diabetes mellitus 11 . NIMA‐related kinase 7 (NEK7), a serine/threonine protein kinase, regulates proper spindle formation and cytokinesis production 12 . Furthermore, being a mitotic kinase, NEK7 is required for the activation of NLRP3 inflammasomes 13 .…”
Section: Introductionmentioning
confidence: 99%